PEMENUHAN HAK PESERTA DIDIK MELALUI AKSESIBILITAS PENDIDIKAN AGAMA - Yuyun Libriyanti (widya balina, 2019)
Abstrak Penyelenggaraan pendidikan agama sudah sewajarnya didasari pada pemenuhan hak peserta didik untuk mendapatkan pendidikan agama sesuai agamanya masing-masing. Pemenuhan hak peserta didik dalam mendapatkan pendidikan agama mengalami sejarah panjang dalam potret pendidikan agama di Indonesia. Memahami urgensi penyelenggaraan pendidikan menjadi hal utama dalam rangka memenuhi hak peserta didik untuk memperoleh pendidikan agama. Dengan merumuskan aksesibilitas pendidikan agama diharapkan pemenuhan hak peserta didik dalam mendapatkan pendidikan agama sesuai agamanya dapat dilaksanakan sesuai dengan peraturan perundang-undangan yang berlaku. Ketersediaan pendidik, penyelenggaraan pendidikan agama serta pemenuhan sarana dan prasarana merupakan indikator kunci dalam memastikan aksesibilitas pendidikan agama telah terpenuhi. Abstrack The implementation of religious education is naturally based on fulfilling the rights of students to get religious education according to their respective religions. Fulfillment of the rights of students in getting religious education experiences a long history in the portrait of religious education in Indonesia. Understanding the urgency of organizing education is the main thing in order to fulfill the rights of students to obtain religious education. By formulating the accessibility of religious education, it is expected that the fulfillment of the rights of students to obtain religious education in accordance with their religion can be carried out in accordance with applicable laws and regulations. The availability of educators, the organization of religious education and the fulfillment of facilities and infrastructure are key indicators in ensuring the accessibility of religious education has been met.